Optimizing the Lithium Phosphorus Oxynitride Protective Layer Thickness on Low‐Grade Composite Si‐Based Anodes for Lithium‐Ion Batteries. Issue 2 (15th January 2018) - Chen, Chih-Jung; Mori, Tatsuhiro; Jena, Anirudha; Lin, Hung-Yu; Yang, Nai-Hsuan; Wu, Nae-Lih; Chang, Ho; Hu, Shu-Fen; Liu, Ru-Shi
Abstract: Composite materials containing Si as a component, are growing importance in the field of Li‐ion battery due to their extremely high theoretical capacity (3500 mAh g −1 at room temperature). However, the capacity of Si anode material decays dramatically because of serious volume variation during lithiation and delithiation process, which lead to deformation of Si electrode and resulted in poor cycle performance. In the present work, we have reported improved performance of modified Si electrode as an anode in Li‐ion battery. Si obtained from kerf‐loss slurry have been alloyed with Ni nanoparticles to improve its conductivity. A mechanistic study of the deposition of LiPON with respect to deposition pressure also presented. It is seen that LiPON layer serves as a protective layer with high ionic conductivity (1.38×10 −6 S cm −1 ) to improve the electrochemical activity of Si−Ni electrode. The optimal 1 st charge capacity of LiPON modified‐ Si−Ni composite was 915 mAh g −1 at a current density of 50 mA g −1 in a potential window of 1.2 V to 0.005 V. The charge capacity retained 56.2% of the initial cycle after 90 th cycling measurement. Abstract : LiPON coated on Si−Ni electrode generates protective layer that can minimize SEI formation. The working pressure in the sputter chamber not only controls the thickness of LiPON coating but also the coordingation of N and P atoms in the molecule. Optimizing the thickness of LiPON layer on the Si−Ni electrode can minimize the artificial SEI formation and hence longer cycle stability.